A calculus clinical study comparing the efficacy of two commercially available dentifrices - Sowinski, J; Battista, G; Petrone, D M; Petrone, M E; DeVizio, W; Volpe, A R; Proskin, H M (The Journal of clinical dentistry, 2000)
The objective of this double-blind clinical study, conducted in harmony with the Volpe-Manhold design for studies of dental calculus, was to compare the effect on supragingival calculus formation of a dentifrice containing pyrophosphate, tripolyphosphate and a copolymer in a 0.243% sodium fluoride/silica base (Test Dentifrice), to that of a commercially available calculus-inhibiting dentifrice containing tetrapotassium pyrophosphate, disodium pyrophosphate, and tetrasodium pyrophosphate in a 0.243% sodium fluoride/silica base (Positive Control Dentifrice). Adult male and female subjects from the Northern New Jersey area were entered into the study, provided a full oral prophylaxis and assigned the use of a placebo (non-calculus-inhibiting) dentifrice for eight weeks. At the completion of this initial period, subjects were assessed for baseline Volpe-Manhold Calculus Index scores, provided another full prophylaxis and stratified into two treatment groups which were balanced for age, sex and baseline calculus. Subjects were instructed to brush their teeth twice daily (morning and evening) for one minute with their assigned dentifrice, using a soft-bristled toothbrush. Examinations for dental calculus were again performed after twelve weeks' use of the study dentifrices. Eighty-nine (89) subjects complied with the protocol and completed the entire study. At the three-month examination, the Test Dentifrice group exhibited a statistically significant 31.0% reduction in the mean Volpe-Manhold Calculus Index score compared to the Positive Control Dentifrice group. The results of this clinical study support the conclusion that a new calculus-inhibiting dentifrice containing pyrophosphate, tripolyphosphate, and a copolymer in a 0.243% sodium fluoride/silica base is efficacious for the control of the development of supragingival calculus, and provides a level of benefit greater than that provided by a commercially available calculus-inhibiting dentifrice containing tetrapotassium pyrophosphate, disodium pyrophosphate, and tetrasodium pyrophosphate in a 0.243% sodium fluoride/silica base.